Геометрические и электрофизические параметры обмотки якоря электромеханического преобразователя инерционного накопителя энергии для пригородного электропоезда - Омельяненко, Галина Викторовна; Оверьянова, Лилия Викторовна; Маслий, Артём Сергеевич (Национальный технический университет "Харьковский политехнический институт", 2020)
Цель. Установление аналитических выражений машинных постоянных и электромагнитных параметров для специфической схемы обмотки якоря электромеханического преобразователя инерционного накопителя энергии в виде обращенной электрической машины постоянного тока с полупроводниковым коммутатором и возбуждением от постоянных магнитов. Методика. Для проведения исследований использована теория электрических цепей, метод участков для нахождения взаимной индуктивности катушек обмотки якоря. Результаты. Установлена связь параметров машинных постоянных, активного и индуктивного сопротивлений с конфигурацией, схемой соединения и геометрическими размерами обмотки якоря. Научная новизна. Для специфических схем якорных обмоток системы электромеханического преобразования энергии инерционного накопителя найдены аналитические выражения машинных постоянных и электромагнитных параметров, которые определяют показатели энергии обмена и мощности накопителя. Практическое значение. Разработанные рекомендации по определению машинных постоянных и электро-магнитных параметров инерционных электромеханических накопителей энергии позволяют оценить свойства устройств такого типа на борту подвижного состава.

Purpose. To establish analytical expressions of machine constant and electromagnetic parameters for a specific circuit of the armature winding of an electromechanical converter of an inertial energy storage device, which is a DC electric machine with a semiconductor switch and excitation from permanent magnets. Methodology. For research the theory of electrical circuits is used to create a mathematical model of the processes of electromechanical energy conversion in an inertial storage device. The plots method is used to find the mutual inductance of the armature winding coils, which are presented in the form of infinitely thin single-turn contours of rectangular shape, located inthreеdimensional space. Results. Mathematical models of the processes of electromechanical energy conversion in an inertial storage device are obtained reflecting the relationship between the exchange energy and drive power with geometric and electrophysical parameters of both the energy accumulator and the system of its electromechanical converter. A connection of the parameters of machine constant, active and inductive resistances with the configuration, wiring diagram and the geomet-ric dimensions of the armature winding has been established. The wiring of sections in the phase ofthe armature winding depends on the required value of the voltage and current of the machine. The possibility of regulating the voltage of the drive by switching on and off the working phases of the systemof electromechanical converter, as well as by changing the angle of the load is shown. Originality. Mathematical models are obtained that relate the indicators of the energy of exchange and the power of the drive to the geometrical and electro physical parameters of both the energy accumulator and the system of its electromechanical converter. A feature of these models is operating with an average value of induction and machine constants when determining the electromotive force and electromagnetic moment. Practical value. Recommendations are developed for determining the machine constant and electromagnetic parameters of electromechanical inertial energy storage devices. This allows to evaluate the properties of devices of this type in the modes of storage and delivery of energy during their operation on board the rolling stock.
Geometric and electrophysical parameters of armature winding of electromechanical converter of inertial energy storage for suburban trains
Keywords: активное сопротивление; индуктивное сопротивление; active resistance; inductive resistance